Secure mobile medical record system for tuberculosis using public key infrastructure and selective encryption of medical images (SuMMeRS) - Roque, Jonas Fabian
Security is implemented on common medical record systems and applications through restriction and control of access to the services they offer. Such implementations suffer vulnerability to password attacks and phishing. As a consequence, these expose all of the data of the system to the intruder. Medical record systems information includes personal and health information of patients which can be described in text and in images. A naive solution consists of the systematic encryption of the entire data. However, such approach would be inconvenient for images since both encryption and decryption process require large amount of computational power. Meanwhile, in the Philippine setup, the concentration of population of doctors and domain experts reside in the urban areas. As a consequence, those who are in rural areas would travel to hospitals in the metro for consultation. In addition, collaboration among experts for certain health cases of patients would require actual presence of the involved doctors. The likes of these situations take an amount of time, money and effort. these domain experts, being also on-the-go, should be able to access the medical records system through mobile wirelessly. SUMMERS focuses on developing a secure medical record software with remote consultation and diagnosis functionalities, a referral system module, an implementation of selective encryption of images particularly on x-ray images through Discrete Cosine Transform and Advanced Encryption Standard, and messaging system with public key infrastructure through OpenPGP. this application can be accessed through a mobile device application and a web application. The personal information, along with the images within the service, are strongly protected by the cryptosystem.